Patients’ Experiences of the Treatment Received During Their Stay in the Stroke Unit at Spanish Healthcare Centers: A Qualitative Approach - Sagrario Pérez-de la Cruz (Medicina)
Background and Objectives: Stroke is a condition that seriously impairs the personal, family, social and professional lives of those affected. The aim of this study was to explore the perceptions of patients who have experienced a stroke and received care in stroke units across various health centers in Spain, as well as to gain insight into their rehabilitation process. Materials and Methods: A qualitative study was carried out with individual interviews involving 30 patients who voluntarily wished to collaborate, recounting their personal experience of the treatment and professionalism with which they were treated in these units. Results: Four themes emerged in this study: healthcare, the role of health professionals in the rehabilitation process, the professional–patient relationship, and barriers and facilitators of this relationship. The participants showed the variability in the care protocols for acute stroke patients, as well as the importance of a close relationship with physiotherapists and the demand for professionalism. Conclusions: The heterogeneity in the implementation of action protocols by healthcare professionals in stroke units has been demonstrated, leading to inequality in the approach and treatment of these patients. These findings may be useful to identify ways of approaching acute patients in stroke units and to design a comprehensive and coordinated rehabilitation program for these patients.